A Giant Vulvar Mass: A Case Study of Cellular Angiofibroma - Ümit Aydın; Hasan Terzi; Ünal Turkay; Ahmet Tuğrul Eruyar; Ahmet Kale (Case Reports in Obstetrics and Gynecology)
Cellular angiofibroma is a mesenchymal tumor that affects both genders. Nucci et al. first described it in 1997. Cellular angiofibroma is generally a small and asymptomatic mass that primarily arises in the vulvar-vaginal region, although rare cases have been reported in the pelvic and extrapelvic regions. It affects women most often during the fifth decade of life. The treatment requires simple local excision due to low local recurrence and no chance of metastasization. The current study presents a case of angiofibroma in the vulvar region that measured approximately 20 cm.